ANALISIS PENDIDIKAN KARAKTERISTIK AKHLAK ANAK USIA SD/MI DI ERA SOCIETY 5.0 - Indriani, Indriani; Putri Pratiwi, Astrid; Jauhara, Jauhara; Mukjizat, Lailatul; Fatimah, Siti (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2022)
This study aims to find out and provide an overview that moral and religious education is very important for children in facing the era of society 5.0. Educational transformation has developed rapidly, along with increasingly developing technology making systems, learning methods, technology and other things change including the character of students. Character education must also be built together by the family, school, and the environment. School is a place that is considered appropriate for the process of forming character education in students. The impact of social character education in the era of society 5.0 on the behavior of elementary school children is as explained that character education is a systematic intentional effort to develop virtues that have a positive impact on both the individual and the social environment and the process is not instantaneous, but through habituation efforts. In preparing for the challenges of the society 5.0 era, the educational curriculum design mentions several substantive points, namely character education, having the ability to think critically and innovatively, and being able to apply technology in the era of society 5.0. seeing how technological developments can affect a person's life, it is necessary to cultivate character, especially in early childhood.